Sustained Lymphatic Delivery of Fibrinogen after Induced Afibrinogenemia - Young, Margaret C.; Kolmen, S. N (Thrombosis and Haemostasis, 1968)
Lymphatic fibrinogen levels were maintained for a long period in the absence of plasma fibrinogen. Although a portion of the additional fibrinogen required may have been the result of de novo synthesis, an additional source, that of previously sequestered fibrinogen in storage sites, must have been present.The amount of fibrinogenolysis induced, although complete in the plasma compartment of dogs, was not as effective in the lymphatic compartment. One resultant of fibrinogenolytic induction in vivo was retardation of fibrin polymerization in incubated lymph samples.